From “open ocean” to “exposed aquaculture”: why and how we are changing the standard terminology describing “offshore aquaculture” - Sclodnick, Tyler; Chambers, Michael; Costa-Pierce, Barry Antonio; Dewhurst, Tobias; Goseberg, Nils; Heasman, Kevin Gerald; Isbert, Wolf; Krause, Gesche; Wieczorek, Daniel; Markus, Till; Buck, Bela H. (Frontiers in Aquaculture, 2024)
The term "offshore" with regards to aquaculture has hitherto encompassed various perspectives, including technology, geographic location, legal jurisdiction, and more. To resolve the ambiguity in this term and understand its implications for current and future aquaculture development, "offshore" should be resolved into two separate metrics: distance from shore and energy exposure. The United Nations Convention on the Law of the Sea (UNCLOS) distinguishes between internal waters, territorial sea, contiguous zone, exclusive economic zone (EEZ), and the high seas, but currently has no precise definition for "offshore" in its provisions, and therefore no applicable laws pertaining to "offshore" aquaculture. Regulating a multi-technology aquaculture sector may require integrating new spatial concepts into the law rather than merely adapting and extending current regulatory designs to include new production concepts. The metrics of distance from shore and exposure are seen as a range rather than a specific threshold, allowing for a continuum. Distance from shore is readily quantified as a distance from a baseline. To rigorously quantify the exposure, the influences and interactions of oceanic parameters (water depth, water current, and wave height and period) were utilized to generate six indices, which are described in Lojek et al. (2024 in review). These oceanic parameters are seen as the main contributions which influence the physical and some biological parameters required for site, species, and technology selection. The indices developed and used in the case studies presented have been shown to be useful tools in the general assessment of the energy that will influence the species and equipment selection at potential aquaculture sites. The indices do not provide a definitive answer as to the potential financial success of a site as this requires other inputs relating to infrastructure costs, annual production, distance from port, sales strategy, etc. However, the Specific Exposure Energy index creates a useful tool to describe site energy and be comprehensible to a wide range of stakeholders. We recommend the SEE index be adopted as the predominant tool to communicate the exposure level of aquaculture sites.